Mekanisme Fungsi Manajemen Keuangan Dan Nilai Perusahaan - Sochib Sochib (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2018)
Corporate value is the main objective of corporate management that is done by combining the functions of financial management through investment decisions, funding decisions and dividend policies will have an effect on the value of the company that is reflected from the share price. This study aims to empirically examine the mechanisms of corporate financial functions such as Investment Decision, Financing Decision, and Dividend Policy, which is pronounced by Price Earning Ratio, Debt to Equity Ratio, to Company Value Proxy Dividend Payout Ratio. Researchers used 11 samples of major trading sector sectors that went public in the period 2011-2015 so that obtained 55 observations. Hypotheses are tested by using regression analysis that can be used to predict the condition of the next few years after knowing the magnitude of the effect of the independent variable. Data analysis to test regreation and influence of independent variable to dependent variable using SPSS. The results obtained in this study that Investment Decision, Decision Funding have a significant effect on Corporate Value, but Dividend Policy has no effect on Corporate Value. It is expected that the results of this research can contribute in the development of Financial Management Science in Indonesia, especially aspects of the factors that affect the Company Value proxyed by Price Book Value